Systematics expertise and taxonomic status of New Zealand’s freshwater insects - Leschen, Richard; Collier, Kevin; Death, Russell; Harding, Jon; Smith, Brian (New Zealand Science Review, 2016)
Insects are important to ecosystem functioning in freshwater habitats. They have a rich diversity, fill every ecological niche, and as predators and scavengers and the prey of larger species, they play a vital role in nutrient cycling. There is no doubt that aquatic insects are under considerable threat in New Zealand (Grainger et al. 2014, Joy & Death 2014, Weeks et al. 2016, Collier et al. 2016). Some freshwater species are iconic to New Zealanders, like the ubiquitous sandflies with aquatic larvae (Craig et al. 2012), but also known to many systematists worldwide are New Zealand’s endemic species, like the primitive dragonfly Uropetalachiltoni Tillyard (Petaluridae) or the ice worm Zelandochlus latipalpis Brundin (Chironomi-dae). To most biologists and almost any informed layperson, aquatic insects (along with a number of other invertebrates) are well-known biological indicators of water quality. The exact number of freshwater insects is unknown, but estimates range from 640–800 described species in New Zealand (McFarlane et al. 2010, Weeks et al. 2016). They exhibit intriguing ad-aptations to their stream environments that include symbiotic relationships (commensalism and phoresy) of chironomid midge larvae with mollusks, flies and mayflies (Forsythe & McCallum 1978, Winterbourn 2004, Cranston 2007), live birth (viviparity) in the caddisfly Triplectides cephalotes (Walker) (Pendergrast & Cowley 1966; Morse & Neboiss 1982) and adaptations to torrential water velocities (e.g. Blephariceridae) that make them interesting model organisms for ecological and evolutionary study (Buckley et al. 2015, McCulloch et al. 2016). New Zealand’s long geographic isolation has led to high levels of regional and national endemism (Gibbs 2006), and biogeographic studies of aquatic insects have helped to reconstruct the geologic and climatic histories of New Zealand’s ancient terrains and weathered landscapes.